The velocity structure of the intracluster medium of the Centaurus cluster. Issue 2 (26th March 2022) - Gatuzz, Efrain; Sanders, J S; Canning, R; Dennerl, K; Fabian, A C; Pinto, C; Russell, H; Tamura, T; Walker, S A; ZuHone, J
ABSTRACT: There are few direct measurements of the intracluster medium (ICM) velocity structure, despite its importance for understanding clusters. We present a detailed analysis of the velocity structure of the Centaurus cluster using XMM–Newton observations. Using a new European Photon Imaging Camera-pn energy scale calibration, which uses the Cu Kα instrumental line as reference, we are able to obtain velocity measurements with uncertainties down to Δ v ∼ 79 km s −1 . We create 2D spectral maps for the velocity, metallicity, temperature, density, entropy, and pressure with a spatial resolution of 0.25 arcmin. We have found that the velocity structure of the ICM is similar to the velocity structure of the main galaxies, while the cold fronts are likely moving in a plane perpendicular to our line of sight with low velocity. Finally, we have found a contribution from the kinetic component of 25 per cent to the total energetic budget for a radius >30 kpc.